IMPORTANCE OF LITHIUM SILICON BATTERY (LI-ION) - Sen, Pawan; Bakliwal, Chandresh; Jain, Samiksha; Shrijal Jaiswal (International Journal of Psychosocial Rehabilitation, 2020)
Lithium silicon battery is a type of Li-ion battery commonly we used graphite as an anode but here we used silicon on the place of graphite as an anode. Comparison of other batteries like Li-Po batteries which mean lithium polymer battery that are more effective, more prevalent and more energy density. In today’s advanced world Li-ion battery is essential for supplying power for a long cycle of time. Li-ion batteries are used in EV, DRONES, ENERY STORAGE SYSTEMS and many ELECTRONICS Devices. We used Li-ion batteries in any places like hot & cold temperature, different environments or even in SPACE. The market of Li-Si batteries has hiked every day. There are some companies that manufacture rapidly LI-ion batteries SONY, XNRGI, GLOBAL GRAPHENE GROUP and many mores. In the past Li-ion batteries were only used for small devices such as mobile, small toys and small electronics devices. There are six types of Li-ion batteries, but most commonly used battery is LCO (lithium cobalt oxide).